PENGARUH FILSAFAT DALAM TAFSIR AL-QUR'AN KONTEMPORER - Kusnadi, Kusnadi; Hawirah (Jurnal Al-Mubarak: Jurnal Kajian Al-Qur'an dan Tafsir, 2025)
The development of contemporary Qur'anic interpretation cannot be separated from the role of philosophy as one of the intellectual approaches in understanding the sacred text. Philosophy, with its rational and systematic tools, offers a new perspective in understanding the complex and contextual meanings of the Qur'an. This article aims to examine the extent of the influence of philosophy in the methods and results of contemporary Qur'anic interpretation. This study uses a qualitative approach with a literature study method on the works of contemporary exegetes such as Muhammad Abduh, Fazlur Rahman, and Nasr Hamid Abu Zayd. The research findings show that philosophical thought provides a strong methodological foundation for interpretation, especially in the hermeneutic approach, rational ethics, and epistemology of revelation. Philosophical-based interpretation of the Qur'an tends to be reflective, rational, and progressive, so that it is able to answer the intellectual and social challenges of modern society. Thus, the integration between interpretation and philosophy not only broadens the horizon of understanding the Qur'an, but also strengthens the relevance of the Qur'an in contemporary life